DESEMPENHO SILVICULTURAL DE EUCALIPTO EM DOIS ARRANJOS POPULACIONAIS NO SISTEMA SILVIPASTORIL - SOUZA, Vitória Cristina di Matheus e; RODRIGUES, Carolina Garcia; BARBOSA, Giselle Feliciani (ANAIS DO ENIC, 2023)
-